Angiographic study of Coronary Artery Dominance in Nepalese Population - Nepal, Rajesh; OM, Anil (Journal of Nobel Medical College, 2016)
Background The dominance of coronary artery in our population is not known. This study aims to identify dominant coronary artery in Nepalese population. Material and Methods This study was carried out in the Cath Lab of Manmohan cardiovascular and thoracic centre Kathamandu over a period of 18 months (August2012 to April 2014). All patients of either gender who presented to the Cath lab for coronary angiography for different indications were included in the study. Patients with congenital heart diseases who were below the age of 18 years were excluded. Results A total of 667 patients were enrolled out of which 69% (n=488) were male and 31% (n=219) were female. The mean age was 51.3(30-76) years. Right coronary artery was dominant in 83%, left dominant in 10 % and co-dominant in 7% of the patient population. Conclusion The right coronary dominant pattern is more prevalent in our population. Gender has no significant association with coronary dominance. Journal of Nobel Medical College Volume 5, Number 1, Issue 8, January-July 2016, 6-8